Monetary and fiscal policy interactions in a New Keynesian model with capital accumulation and non-Ricardian consumers - Campbell Leith; Leopold von Thadden (Deutsche Bundesbank, 2006)
This paper develops a small New Keynesian model with capital accumulation and government debt dynamics. The paper discusses the design of simple monetary and fiscal policy rules consistent with determinate equilibrium dynamics in the absence of Ricardian equivalence. Under this assumption, government debt turns into a relevant state variable which needs to be accounted for in the analysis of equilibrium dynamics. The key analytical finding is that without explicit reference to the level of government debt it is not possible to infer how strongly the monetary and fiscal instruments should be used to ensure determinate equilibrium dynamics. Specifically, we identify in our model discontinuities associated with threshold values of steady-state debt, leading to qualitative changes in the local determinacy requirements. These features extend the logic of Leeper (1991) to an environment in which fiscal policy is non-neutral. Naturally, this non-neutrality increases the importance of fiscal aspects for the design of policy rules consistent with determinate dynamics.
Keywords: E63; E52; 330; Monetary policy; Fiscal regimes; Geldpolitik; Finanzpolitik; Regelgebundene Politik; Ungleichgewichtstheorie; Dynamisches Gleichgewicht; Ricardianisches Äquivalenztheorem; Theorie